Bioethics and Politics - Sgreccia, Elio (Medicina e Morale, 1987)
Bioethics is at a significant turning point: from university chairs, where it has just appeared, it is about to move into political and parliamentary arenas. It is actually a hairpin turn or a return to the political arena. It is well known that bioethical reflection was born after the Nuremberg trial to give theoretical substance to the proclamations of some of the main 'human rights' that were gradually being formulated, starting with the 'Universal Declaration of Human Rights' by the UN on 10 December 1948, just 40 years ago: the right to life, to physical integrity, to the protection of health, for every man, of every culture and religion, together with the other rights to freedom, association, culture, etc., which are the cultural heritage of every free society. which are the cultural heritage of every free and worthy society.